2008
DOI: 10.1371/journal.pcbi.1000025
|View full text |Cite
|
Sign up to set email alerts
|

Neural Coding of Natural Stimuli: Information at Sub-Millisecond Resolution

Abstract: Sensory information about the outside world is encoded by neurons in sequences of discrete, identical pulses termed action potentials or spikes. There is persistent controversy about the extent to which the precise timing of these spikes is relevant to the function of the brain. We revisit this issue, using the motion-sensitive neurons of the fly visual system as a test case. Our experimental methods allow us to deliver more nearly natural visual stimuli, comparable to those which flies encounter in free, acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
112
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 40 publications
(66 reference statements)
6
112
0
4
Order By: Relevance
“…Using information-theoretic measures it was found that the temporal precision of the auditory information coding is coarser than 1 ms, but finer than 5 ms (Kayser et al, 2010). Similar findings hold for visual (Victor and Purpura, 1996; Butts et al, 2007) and other temporal tasks (Nemenman et al, 2008), with the consensus that the required precision for spike arrival timing was on the order of few or several milliseconds. In some specialized circuits, at the system level, the timing constraints can be at the sub-millisecond range.…”
Section: Introductionsupporting
confidence: 62%
“…Using information-theoretic measures it was found that the temporal precision of the auditory information coding is coarser than 1 ms, but finer than 5 ms (Kayser et al, 2010). Similar findings hold for visual (Victor and Purpura, 1996; Butts et al, 2007) and other temporal tasks (Nemenman et al, 2008), with the consensus that the required precision for spike arrival timing was on the order of few or several milliseconds. In some specialized circuits, at the system level, the timing constraints can be at the sub-millisecond range.…”
Section: Introductionsupporting
confidence: 62%
“…MI has been used to compare different neural response codes [Ince et al, 2013; Kayser et al, 2009; Reich et al, 2001], characterize different neurons [Sharpee, 2014] as well as quantify the effect of correlations between neurons [Ince et al, 2009, 2010; Moreno‐Bote et al, 2014] and the importance of spike timing [Kayser et al, 2010; Nemenman et al, 2008; Panzeri et al, 2001]. Recent studies have begun to explore its application to neuroimaging [Afshin‐Pour et al, 2011; Caballero‐Gaudes et al, 2013; Gross et al, 2013; Guggenmos et al, 2015; Ostwald and Bagshaw, 2011; Panzeri et al, 2008; Salvador et al, 2007; Saproo and Serences, 2010; Schyns et al, 2011; Serences et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…How motion information is encoded by fly motion sensitive wide-field neurons has already been analyzed under outdoor conditions. For methodological reasons, these studies could only address the neural responses to rotational displacements of the animal (Egelhaaf et al, 2001; Lewen et al, 2001; Nemenman et al, 2008). Therefore, they had to focus on how reliably self-rotations are represented by the visual motion pathway, but could not address how spatial information is represented.…”
Section: Introductionmentioning
confidence: 99%